Pembimbingan Guru Untuk Karakter Siswa Di Era Digital - Nurmiati Marbun; Lamtiur Pasaribu; Elia Yenny (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2020)
Abstract:Guiding the character of students in modern times is not an easy thing, because the character of students in the digital era is very different from the character of students in the past. Students in the past were easy to manage and direct, but in the digital era students are very difficult to manage, direct and advise, because they have different lifestyles. Children in the digital era have been shaped and influenced by technological developments. Just look at the lifestyle of school children today, they can already enjoy super-fast mobile Internet services. Not only enjoying the sophistication of the technology, but being able to do anything via a smartphone, ranging from entertainment, study, work, and so on. One of the negative impacts of technological developments on the renewal of student character in the digital era is that the moral decline among the community, especially teenagers and students, is one of the serious socio-cultural challenges. So a teacher must really realize that their status is not only seen by people as a profession but teachers are also seen as people who are trusted to teach, educate and guide students to build character in this digital era.Keywords: Guidance; character; digital era. Abstrak:Membimbing karakter Siswa di zaman modern ini bukan hal yang mudah, karena karakter siswa di era digital sangat berbeda dengan karakter siswa di zaman dulu. Siswa di zaman dulu mudah diatur dan diarahkan, tetapi di era digital siswa sangat susah diatur, diarahkan dan dinasihati, karena mereka memiliki pola hidup yang berbeda-berbeda. Anak-anak di era digital telah terbentuk dan dipengaruhi oleh perkembangan teknologi. Lihat saja gaya hidup anak-anak sekolah di zaman sekarang, mereka sudah bisa menikmati layanan mobile Internet yang super cepet. Bukan hanya menikmati kecanggihan teknologi tersebut, namun bisa melakukan apapun lewat smartphone, mulai dari entertainment, belajar, kerja, dan sebagainya. Salah satu dampak negatif tentang perkembangan teknologi terhadap pembaharuan karakter siswa di era digital adalah kemerosotan moral di kalangan masyarakat khususnya remaja dan pelajar/siswa menjadi salah satu tantangan sosial budaya yang serius. Jadi seorang guru haruslah benar-benar menyadari bahwa status mereka bukan hanya dipandang orang sebagai sebuah profesi namun guru juga dipandang sebagai  orang yang dipercaya untuk mengajar, mendidik dan membimbing untuk membangun karakter siswa di era digital ini.Kata Kunci: Pembimbingan; karakter; era digital.